RISK ASSESSMENT MODEL FOR INTERNAL AUDIT OBJECTS ACTIVITIES IN AUDITING PLANNING PROCESS - Кійко , Юрій (Socio-economic relations in the digital society, 2019)
The present article deals with traditional methods for assessing the riskiness of the bank’s units activities and processes which are the objects of audit. In this research we worked with international standards, domestic practice and theoretical scientific developments. There we identified the main shortcomings of such approaches and proposed a new assessment model with a minimal human factor infl uence. An important role in effective audit organization is to have detailed planning, which is based more on the numerical quality indicators of the internal audit objects activity. There we advocate the adoption of an integrated accounting system in Ukrainian banks and its role for risks calculations.